Territories, lines and bodily practices: the geomorphological dimension of school Physical Education (Práxis Educativa, 2024)
This article aims to conceptualize what it is called the geomorphological dimension of Physical Education, and it proposes territorial body practices as an object of study. To this end, combined mainly with Gilles Deleuze and Félix Guattari, it goes through some concepts such as territory, rhythm, ritornello to establish new perspectives on the post-critical notion of culture and body culture – which, as described, is much more associated with a genealogical perspective today. In this sense, it uses the concept of spirals as a centripetal force that contains the lines of desire and territorializes bodily practices in certain ways. Finally, it invites the teacher to assume the position of a traveler among these distortions, always attentive to a specific objective: undoing (micro)fascist agencies.Keywords: School Physical Education. Gilles Deleuze and Félix Guattari. Territory.